PERAN STRATEGIS ‘AMIL ZAKAT DALAM MEMASTIKAN EFEKTIFITAS IBADAH ZAKAT YANG BERORIENTASI KESEJAHTERAAN SOSIAL - Nasrullah Nasrullah (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2018)
Changes and developments in legal conclusion of law must be preceded by studies that respect to certain legitimate methods and rules; likewise, ‘Amil Zakat. Essentially, its conceptual existences and fundamentals have been provided by Shari'ah texts, both in the A-quran, Hadith, yet in Atsar transmissions. In a normal circumstance, legal actions for managing zakat through Amil can be applied directly. However, the development of the zakat theory, the increase of business incomes, quality change of “rich” meanings, the difference of place and time, the potential quantity of revenue and distribution, also generate the changes of the study about ‘Amil Zakat. The ideal idea of ​​the Al-Qur’an utilized